Simultaneous reduction of dietary protein and daily feeding rate in biofloc system: Effect on water quality, growth, digestive and antioxidant capacity, immune response, and resistance to Aeromonas hydrophila in common carp - Hossein Adineh; Mahdi Naderi; Mohammad Amini Chermahini; Golbahar Zeitounli; Mohammad Meysam Salahi Ardekani (Aquaculture Reports)
This experiment evaluated the impacts of simultaneous reduction of dietary protein and daily feeding rate in a biofloc system on performance of common carp, Cyprinus carpio. Juveniles (19.70 ± 1.55 g) were randomly placed in 15 tanks (200 L, 50 fish per tank) and divided into five groups including fish fed diets containing 35 % protein at 3 % (P35–3 %) or 2 % (P35–2 %) body weight (BW) per day and diets containing 25 % protein at 3 % (P25–3 %) or 2 % (P25–2 %) BW per day in biofloc culture system, and control group (clear water system, 35 % dietary protein, 3 % BW). Each group had three tanks. After 60 days, fish were exposed to Aeromonas hydrophila and the relative percentage survival (RPS) was determined. The lowest level of total ammonia was obtained in P25–2 % tanks. Higher growth of fish was obtained in P35–2 %, but it was not significantly different from the P25–2 % (P > 0.05). P35–2 % and P25–2 % groups had higher amylase and lipase activities compared to P25–3 % and control (P < 0.05). Higher antioxidant enzyme (CAT, SOD, and GPx) activities and lower liver malondialdehyde were obtained in P35–2 %, P25–2 %, and P25–3 % groups compared to P35–3 % and control (P < 0.05). Serum alternative complement (ACH50) activity was highest and cortisol level was lowest in P35–2 % and P25–2 % groups. Serum lysozyme activity was significantly higher in P35–2 % group than the P35–3 % and control (P < 0.05). Serum total immunoglobulin content was highest in P25–2 %. At 5 days after challenge, the RPS was highest in P35–2 % and P25–2 % and lowest in control, which can be described by using more bioflocs at a lower feeding rate. Overall, it is recommended to the aquaculture industry to reduce dietary protein from 35 % to 25 % and daily feeding rate from 3 % to 2 % BW simultaneously in biofloc system for common carp juveniles.